Comparative floral anatomy of Rhynchospora consanguinea and Rhynchospora pubera (Cyperoideae, Cyperaceae) - Monteiro, Mariana M. [UNESP] (2017)
Rhynchospora is one of the most species-rich genera of Cyperaceae and one of the few with entomophilous species. Considering the few anatomical studies of the genus, especially of the reproductive structures, this study comparatively analysed the anatomy of flowers of two representative species of Rhynchospora, R. consanguinea and R. pubera, including the floral vasculature and the anatomy of the style base, which is persistent with the fruit. Both species have congested inflorescences with light-coloured bracts and bisexual flowers, and phenolic idioblasts in the anthers and gynoecium, characteristics that suggest insect pollination. In R. consanguinea, the bisexual and the most proximal male flower has perianths, a new character state reported for the genus. The floral vasculature pattern is similar in both species, but differs from that previously described for Rhynchospora. In both species, there are two vascular bundles in the rachilla, which split into three receptacular bundles, the latter forming a vascular plexus where the bundles of stamens, gynoecium and ovule are connected. No lateral carpellary trace was observed, and the presence of the abaxial receptacular bundle was interpreted as a vestige of the tricarpellate ancestral condition. In the fruit of both species, the thickened style base (stylopodium) has a parenchyma with idioblasts containing phenolic compounds and idioblasts with helical or reticulate cell wall thickenings. The stylopodium is a homologous structure in the species of Rhynchospora and to other genera of Cyperoideae and evolved several times in the subfamily.